2012
DOI: 10.1038/emboj.2012.142
|View full text |Cite
|
Sign up to set email alerts
|

A dual function of Bcl11b/Ctip2 in hippocampal neurogenesis

Abstract: The transcription factor Bcl11b/Ctip2 promotes hippocampal progenitor proliferation and neural differentiation in a non-cell autonomous manner by regulating the expression of the cell adhesion molecule Desmoplakin. Forebrain-specific ablation causes defective spatial learning and memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
161
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(166 citation statements)
references
References 57 publications
(87 reference statements)
5
161
0
Order By: Relevance
“…NeuroD is expressed in mitotic stages 2b/3 and early postmitotic cells 14 . We have shown previously that the number of NeuroD positive cells is significantly increased in Bcl11b conditional mutants indicating an arrest of neuronal differentiation 8 . While the number of GFP positive cells alone and GFP/NeuroD positive cells did not differ in control and mutant cells a significant increase in NeuroD positive cells was observed in the dentate gyrus where cells had received Cre recombinase ( Figure 2C; this figure has been modified from 8 ).…”
Section: Representative Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…NeuroD is expressed in mitotic stages 2b/3 and early postmitotic cells 14 . We have shown previously that the number of NeuroD positive cells is significantly increased in Bcl11b conditional mutants indicating an arrest of neuronal differentiation 8 . While the number of GFP positive cells alone and GFP/NeuroD positive cells did not differ in control and mutant cells a significant increase in NeuroD positive cells was observed in the dentate gyrus where cells had received Cre recombinase ( Figure 2C; this figure has been modified from 8 ).…”
Section: Representative Resultsmentioning
confidence: 99%
“…We have shown previously that the number of NeuroD positive cells is significantly increased in Bcl11b conditional mutants indicating an arrest of neuronal differentiation 8 . While the number of GFP positive cells alone and GFP/NeuroD positive cells did not differ in control and mutant cells a significant increase in NeuroD positive cells was observed in the dentate gyrus where cells had received Cre recombinase ( Figure 2C; this figure has been modified from 8 ). Finding NeuroD positive cells not only in cells which had received Cre recombinase but also in wild-type cells suggested that indirect mechanisms are involved in Bcl11b regulation of neuronal cell differentiation.…”
Section: Representative Resultsmentioning
confidence: 99%
See 3 more Smart Citations